Determinants Of Livelihood Diversification In An Integrated Agricultural And Non –Agricultural Livelihood System In Ghana - Kolog,J.D.; Asem,F.E.; Mensah-Bonsu ,A.; Atinga,R.A. (Scientific African, 2024)
The diversification of livelihoods by households has been widely acknowledged as a way to overcome food insecurity and poverty challenges in developing countries. Diversification of livelihoods helps spread the risk among multiple livelihood earning activities to provide households with a range of their food needs all year round. By examining the integrated livelihood systems of 405 rural farm households in the Upper East Region of Ghana, empirical evidence is provided in this study using the Sustainable Livelihoods Framework to advance arguments in the literature for the creation of sustainable strategies that improve diversified livelihood systems. The mean diversification indices estimated were 0.45 for agricultural diversification systems, 0.32 for non-agricultural diversification systems and 0.59 for integrated agricultural and nonagricultural diversification systems. With the use of the Cragg two-step regression model, we demonstrate that the decision to diversify and the extent of diversification of rural livelihoods are distinct decisions and are influenced by distinct sets of factors. Similarly, for the three categories of livelihood diversification studied, the effect of these factors also differed. The results emphasize the significance of access to good road network, credit and market information in encouraging rural farm households to diversify their livelihoods. In the short term, improving access to credit and market information through community-based initiatives can provide immediate support to rural households. Communities should also organize local markets and cooperatives to strengthen their economic resilience. While government and stakeholders should focus on long-term infrastructure projects, these community actions can complement such efforts and contribute to achieving global and regional goals targeting food insecurity and poverty eradication.
Keywords: Integrated agricultural and non-agricultural livelihood systems; Livelihood diversification; Ghana